Innovation Policy and Startup Ecosystem of Finland - Linhartová, Kateřina (2023)
The aim of this thesis is to identify and verify the key elements of success of the Finnish startup ecosystem. At the beginning, this thesis offers a comprehensive overview of the startup ecosystem in Finland, analyzing government incentives and the business environment through a review of existing literature. To follow this topic even deeper, there is a data analysis to provide insights into key metrics such as startup numbers, research and development, and venture capital investments. Overall, the first half aims to identify critical success factors of the Finnish startup ecosystem. Finally, the qualitative research presents in-depth interviews with various stakeholders from different parts of the ecosystem to validate the key findings and conclusions drawn from the previous sections.